A Rapid Bonding Method for Fabricating Mixing Microfluidic Chip Based on Micromachining Technology. (17th October 2020) - Wang, Junyao; Hou, Qi; Liu, Huan; Sun, Qi; Yuan, Hengyi
Abstract : In this paper, a rapid bonding method is reported to fabricate a mixing microfluidic chip. The chip is composed of a glass upper plat and a polyurethane bottom plat. The upper plat with a microchannel is obtained through micromachining technology. And the bottom plat is manufactured via mixing the solution with the component of isocyanic acid and polyether polyol. The influence of the solution's proportion on the contact angle and bonding force is investigated to enhance the hydrophilicity and the bonding strength. Furthermore, a mixing experiment is implemented to verify the chip's bonding effect. The experimental results demonstrate that with increasing the proportions of isocyanic acid and polyether polyol, the contact angle and the bonding force increase at first and then decrease gradually. That is attributed to the variation of internal porous structure for different proportions. Considering the contact angle and the bonding force synthetically, the optimal proportion of 3.7 w/w is confirmed. The mixing efficiency is increased from 0.157 to 0.824. Compared with other bonding methods, the method in this paper has the advantages of high efficiency and high bonding strength.